Self-powered environmental monitoring via a triboelectric nanogenerator. (July 2022) - Chang, Austin; Uy, Cameron; Xiao, Xiao; Xiao, Xiao; Chen, Jun
Abstract: With air pollution increasing around 75% in the past 30 years, 80% of the globe's wasted water flowing into Earth's oceans and rivers untreated, and more than 22 million hectares of soil being polluted, a more effective, efficient, and self-sufficient chemical sensor is needed to recognize, and in some cases, treat these pollutants. Currently, many sensors that require an external power source such as a battery or capacitor, necessitate human maintenance and involvement for accurate data collection, and can be detrimental to the environment. This makes the current technology highly unfavorable and incompatible with the recent surge in the Internet of Things (IoT). With that said, with the recent advances in Triboelectric Nanogenerators (TENGs), chemical sensors are able to become smaller, smarter, and most importantly, self-powered. In this review, the research progress of triboelectric nanogenerators for environmental monitoring are systematically summarized. More specifically applications including air, soil, and water chemical sensing will be examined. We concluded our review with a discussion of the challenges and problems of leveraging triboelectric nanogenerators for self-powered environmental monitoring. Graphical Abstract: ga1 Highlights: The chemical sensing capabilities of TENGs for environmental monitoring in the air, water, and soil are systematically summarized. With the recent advances in triboelectric nanogenerators, chemical sensors are able to become smaller, smarter, and most importantly, self-powered. Developments in this field could yield a more sensitive and environmentally friendly solution to detecting chemical pollutants in dense urban regions. Progressive studies have shown alternative, low cost, methods of synthesizing the nanogenerators, pushing these sensors towards practical applications.